Buildings and Facilities Maintenance Projects in Nigerian Universities: An Institutional Leadership Approach - Adindu Chinedu Chimdi; Okorie Victor Nnnanaya; Abdulhaqq, Muhammed Onoruoyiza (International Journal of Contemporary Sciences (IJCS), 2024)
Top university management has decisive roles to play in creating a maintenance culture of university buildings and facilities. Quality and functional buildings and facilities not only promotes healthy living within the university community, but also enhance student’s academic performance. This study examines the top university management leadership roles and behaviours in term of maintenance of buildings and facilities in their universities. Descriptive survey was employed with structured questionnaire as research design and administered to five randomly selected universities in the South-South geopolitical zone of Nigeria. The questionnaires were administered to Directors of works and physical planning units, Directors of budget and planning, Directors of maintenance units and manages in the offices of works and physical planning, budgeting and maintenance units of the three selected federal universities and two State universities in the study area